2006
DOI: 10.1080/00016480500452558
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin expression is associated with poor oncologic outcome in oral and oropharyngeal carcinoma

Abstract: The mean MVDs were 3.6 and 3.1 in pN+ and pN0 groups, respectively (p>0.05). The mean CD105-assessed MVDs were 4.7 in the group with locoregional recurrence and 2.9 in the group without locoregional recurrence or post-treatment diagnosis of distant metastasis (p=0.01). The mean CD105-assessed MVD in primary oral and oropharyngeal SCCs with poor oncological outcome (recurrence of disease or occurrence of distant metastasis) was 4.3. The mean MVD in primary oral and oropharyngeal SCCs with good outcome was 2.9. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…The angiogenic process plays a key role in creating a neo-capillary network and is required for cancer growth, progression, and metastasis 53 . In spite of the importance of angiogenesis for tumour development, only a few studies have been performed examining the prognostic value of angiogenesis biomarkers in OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The angiogenic process plays a key role in creating a neo-capillary network and is required for cancer growth, progression, and metastasis 53 . In spite of the importance of angiogenesis for tumour development, only a few studies have been performed examining the prognostic value of angiogenesis biomarkers in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of neo-vascularisation using CD105 expression has been considered a potential predictor of prognosis in different solid malignancies 52 . It has been shown that the evaluation of micro-vessel density through CD105 expression in primary OSCC may identify patients at risk of recurrence of the disease or poor outcome following treatment 12,53 . In another study performed only on biopsies of early tongue squamous cell carcinomas staged as T1 or T2, CHUANG et al 14 also demonstrated that CD105 expression was a significant and independent prognostic predictor of a worse prognosis.…”
Section: Cd105mentioning
confidence: 99%
“…There is little or no endoglin expression in the vascular endothelium of normal tissues, making it a more specific and sensitive marker of tumour angiogenesis than others commonly used 7. Endoglin has shown promise as prognostic parameter in head and neck,12 oral, pharyngeal and laryngeal carcinomas 8 13…”
Section: Introductionmentioning
confidence: 99%
“…As regards the tumor microenvironment, angiogenesis is considered to be a fundamental process in tumor growth and metastasis [5]. Moreover, angiogenesis has been considered to be one of the most important factors which influence the efficacy of radiotherapy and/or chemotherapy for the treatment of malignant tumors [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%